PENGARUH FANATISME TERHADAP BENTUK PERILAKU AGRESI VERBAL SUPORTER SEPAKBOLA DI MEDIA SOSIAL - Arya Hidayat Syam; Asniar Khumas; Faradillah Firdaus (Tamilis Synex: Multidimensional Collaboration, 2024)
Verbal aggression behavior among football supporters on social media has become an increasingly relevant issue due to the rapid development of technology and social media platforms. This study aims to investigate the influence of fanaticism on verbal aggression behavior of football supporters on social media. A quantitative approach was employed, involving respondents from active football supporters on social media. Data were collected through a Google Form survey measuring levels of fanaticism and verbal aggression behavior on social media. The research sample comprised 508 football supporters who use Twitter. The measurement tools used in this study were the Fanaticism Scale and the Verbal Aggression Scale. Data were analyzed using the ordinal regression technique with the assistance of IBM SPSS version 26 for Windows. The research findings indicate that there is a significant influence of fanaticism on verbal aggression behavior among football supporters on social media (r = 0.055 and p < 0.003). This suggests that as football supporters become more fanatic, it may influence their verbal aggression behavior on social media platforms like Twitter. This research has important implications in the field of social psychology, providing insights for football supporters and social media users.